Propuesta para implementar la gestión por procesos en una organización manufacturera con producción continúa (2017)
In this paper a bibliographic review is made on the principles of process management and its advantages, with the purpose of making a proposal to implement the management by processes in a manufacturing organization of continuous production. In parallel, the different processes identified in companies of the manufacturing sector are reviewed, using a tool that allows a quick identification of the processes that make up the organization′s management. Subsequently a classification of processes and the illustration of them in a map of processes.